PILIHAN BAHASA MASYARAKAT SAM IN DALAM RANAH KELUARGA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The language choice of Samin society in Blora is an interesting phenomenon to study by the perspective of sociolinguistic since it is related not only to languageaspect. but also to socio-cultural aspect.This study a ims to revealthe formof family language choice of Samin societyin Blora and the socio-cultural factors that determine it. This researchis a sociolinguistic study which is based on the language and culture phenomenon in relation to society. In communicating among their family. Samin society use ngoko (low language level) Javanese. madya/krama (middle/high language level) Javanese do switch code and mixed code. either from the ngoko Javanese to madya/krama Javanese or the viceversa.